Mobile smart door security system - Cha Hweay Rhunn, Tommy; Anis Farihan, Mat Raffei; Nur Shamsiah, Abdul Rahman (2021)
Door have interconnection between the different interiors or departments and it is function to preserve privacy and protection for the areas when it is locked. Although there are several solutions for door lock such as using personal identification number, radio frequency identification or biometric system, these systems still have several limitations such as forget password, misplace card or error due to biometric sensor sensitivity. Hence, a smart door security system using a secret knock as well as mobile application are developed to resolve the problem. The developed system is not only can lock or unlock the door using secret knock, but also can monitor any user access the door through mobile.